Tailoring the microstructure and electrical performance of ZnO varistor ceramics via SrTiO₃ doping - Norni Hidayawati, Mat Daud; Muhamad Syaizwadi, Shaifudin; Idza Riati, Ibrahim; Nursabrina Amirah, Mohd Nasir; Abdul Mu’iz Aniq Aiman, Mohd Suhaimi; Mohd Sabri, Mohd Ghazali; Nor Hazmin, Sabri; Mohd Hafiz, Mohd Zaid (Springer Nature, 2026)
In this study, the effect of strontium titanate (SrTiO3) doping on the microstructural evolution and electrical characteristics of zinc oxide (ZnO) varistors is investigated. The ZnO-SrTiO3 ceramic was synthesized using a two-stage sintering technique. Microstructural analysis using X-Ray Diffraction (XRD) reveals the formation of Zn2TiO4 spinel phase, while scanning electron microscopy (SEM) and energy dispersive X-ray (EDX) analysis confirm the segregation of Sr-rich secondary phases at the grain boundaries and triple points. The microstructure and densification were significantly enhanced at the optimum SrTiO3 concentration, thereby improving the electrical properties of the fabricated varistor, with the nonlinear coefficient (α) increasing to 5.49 and the leakage current density (JL) decreasing to 298 μA/cm2 . This investigation provides a deeper understanding of dopants’ influence on ZnO varistors, thereby facilitating the development of more effective and reliable surge protective devices, especially for low-voltage applications.